Relationships between Skin Carotenoid Levels and Metabolic Syndrome - Yuji Takayanagi; Akira Obana; Shigeki Muto; Ryo Asaoka; Masaki Tanito; Igor V. Ermakov; Paul S. Bernstein; Werner Gellermann (Antioxidants, 2021)
Carotenoids have potential antioxidant and anti-inflammatory effects; their protective roles are of particular interest in the pathogenesis of metabolic syndrome (MetS). The reflection spectroscopy method has been recently developed to noninvasively measure skin carotenoid (SC) levels, which highly correlates with serum concentration of carotenoids. The relationship between SC levels and metabolic syndrome has been investigated. We aimed to identify the differences in patient characteristics and SC levels between participants with and without MetS in a large health examination population. In addition, the relationships between SC levels and various clinical parameters related to MetS were investigated. SC levels were measured using a reflection spectroscopy. A total of 1812 Japanese participants (859 male, 953 female; mean age ± standard deviation (SD), 57.8 ± 11.0 years) comprised the study population, i.e., participants with MetS (n = 151) and those without MetS (n = 1661). Multivariate logistic regression analysis was performed to identify variables associated with MetS. Compared to controls (377.3 ± 122.8), SC indices were significantly lower in patients with MetS (340.7 ± 112.5, p = 0.0004). Multivariate models also suggested that lower SC was significantly associated with MetS after adjustment for age, sex, smoking habit, and other potential risk factors for MetS. Furthermore, male gender (p < 0.0001), smoking habit (p < 0.0001) and worse lipid profiles (i.e., serum triglyceride (r = −0.1039, p < 0.0001), high-density lipoprotein (r = 0.1259, p < 0.0001), and usage of hypolipidemic agents (p = 0.0340)) were significantly associated with lower SC levels. The current study indicated that lower SC levels were significantly associated with MetS. This study highlights the antioxidant capacity of carotenoids in patients with MetS and the clinical utility of non-invasive and cost-effective SC measurement to detect participants who are at risk of developing MetS in a large population.